Sustainable procurement: a case study on Standard Bank Limited, Bangladesh - Abedin, Md. Jaynul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.